Melastomataceae endémicas del Perú - León, Blanca (2006)
The Melastomataceae are represented in Peru by 43 genera and 660 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mostly shrubs and trees. Here we recognize 169 species and 13 infraespecific taxa as endemics, in 26 genera. Miconia is the genus with the largest number of endemic species. Endemic Melastomataceae are found mainly in Very Humid Montane, Very Humid Premontane Forests and Humid Lowland Amazonian Forests regions, between 100 and 3500 m elevation. We applied IUCN categories and criteria to 83 taxa. Apparently, 29 endemic taxa have been recorded within Peru´s protected areas system.